Personal and Psychosocial Risk Factor for Low Back Pain among Automotive Manual Handling Workers in Selangor, Malaysia. - Noor Sazarina Mad Isa @ Yahya; Baba Md Deros; Mazrura Sahani; Ahmad Rasdan Ismail (Universiti Kebangsaan Malaysia, 2013)
It is well known that low back pain among working population is a global problem throughout the world. However, the current situation of occupational low back pain in Malaysia is still vague due to limited number of studies conducted locally.